Do Family Backgrounds Control Students’ Motivation and Achievement in Learning a Foreign Language? The Case of One Islamic Senior High School in Jambi - Ana Wahyuni Arib (Ta'dib: Jurnal Pendidikan Islam, 2017)
The purpose of this mixed methods study was to explore the relationship between family backgrounds of senior high school students and their motivation and achievement in learning English at one Islamic senior high school in Jambi city. Data were collected through questionnaire, interview, and written document (students’ English scores). Data were analyzed by using descriptive statistics and Pearson Product Moment Correlation while interview data were categorized to support the quantitative data. It was found that first there was no significant relationship between family backgrounds (parents’ occupation and educational background) and students’ motivation at Islamic senior high school in learning English. Second, there was no significant relationship between family backgrounds (parents’ occupation and educational background) and students’ achievement at Islamic senior high school in learning English. Based on the result of interview data analysis, it found that there were lacks of parents’ roles in students’ achievement. This study provided information for policy makers, school leaders, researchers, and teacher educators to understand how the relationship between family backgrounds, motivation, and achievement in learning English at the school level.